Dynamics of return and sustainable reintegration in a 'mobile livelihoods'-perspective - Finn Steputat (Danish Institute for International Studies (DIIS), 2004)
Reviewing current literature on return and reintegration processes, this working paper argues that the mobile livelihood patterns and capacities of displaced populations must be taken into account when donors and agencies plan and support such processes. Seen in this perspective, `sustainable return' may involve continued mobility within and across borders. The working paper lists a number of tasks which involved agencies may undertake in support of return and reintegration of displaced population in regard to information, access to land and property, and development. – – Dette arbejdspapir samler aktuel litteratur om repatriering og reintegrationsprocesser og argumenterer for at donorer og hjælpeorganisationer bør tage højde for hvordan geografisk mobilitet indgår i fordrevne befolkningsgruppers livsstrategier. Set i dette perspektiv udelukker `bæredygtig tilbagevenden' ikke at mobilitet fortsat kan indgå i livsstrategierne. Der gives en række anbefalinger om mulig støtte til repatriaerings- og reintegrationsprogrammer.
Keywords: 330; Rückwanderung; Soziale Integration; Flüchtlinge